TEACHERS' DIFFICULTIES IN IMPLEMENTING THE 2013 CURRICULUM AT THE MADRASAH IBTIDAIYAH LEVEL - Muhammad Afif Agistiannur; Salamah (International Journal of Multidisciplinary Reseach, 2025)
This research aims to uncover the various difficulties faced by teachers in implementing the 2013 Curriculum (K-13) in Madrasah Ibtidaiyah (MI). Through a descriptive qualitative approach, data was collected through in-depth interviews, observations, and documentation of MI teachers who have implemented K-13. The results of the study showed that teachers had difficulties in understanding the basic concepts of the curriculum, preparing lesson plans such as lesson plans, carrying out thematic and scientific learning, and in implementing authentic assessments as a whole. External factors such as administrative burden, lack of training, and limited support facilities also exacerbate this condition. This study also found a gap between the national curriculum policy and the real conditions in madrasas. Therefore, a strategy to increase teacher capacity, simplify administration, and provide more contextual curriculum assistance is needed so that the implementation of K-13 in MI can run more optimally and meaningfully. These findings make an important contribution to the development of education policies that are more adaptive to the needs of teachers in madrasas.